Tailspin [compact disc, unabridged] - Brown, Sandra, 1948- (Hachette Audio, 2018)
Rye Mallet is a pilot with a reputation for delivering cargo to far-off locations. But after a sabotage attempt leads to a crash landing, Mallet becomes involved something bigger than a delivery.